Use of a Ray-Based Reconstruction Algorithm to Accurately Quantify Preclinical MicroSPECT Images - Bert Vandeghinste; Roel Van Holen; Christian Vanhove; Filip De Vos; Stefaan Vandenberghe; Steven Staelens (Molecular Imaging)
This work aimed to measure the in vivo quantification errors obtained when ray-based iterative reconstruction is used in micro-single-photon emission computed tomography (SPECT). This was investigated with an extensive phantom-based evaluation and two typical in vivo studies using 99m Tc and 111 In, measured on a commercially available cadmium zinc telluride (CZT)-based small-animal scanner. Iterative reconstruction was implemented on the GPU using ray tracing, including (1) scatter correction, (2) computed tomography-based attenuation correction, (3) resolution recovery, and (4) edge-preserving smoothing. It was validated using a National Electrical Manufacturers Association (NEMA) phantom. The in vivo quantification error was determined for two radiotracers: [ 99m Tc]DMSA in naive mice ( n = 10 kidneys) and [ 111 In]octreotide in mice ( n = 6) inoculated with a xenograft neuroendocrine tumor (NCI-H727). The measured energy resolution is 5.3% for 140.51 keV ( 99m Tc), 4.8% for 171.30 keV, and 3.3% for 245.39 keV ( 111 In). For 99m Tc, an uncorrected quantification error of 28 ± 3% is reduced to 8 ± 3%. For 111 In, the error reduces from 26 ± 14% to 6 ± 22%. The in vivo error obtained with “ m Tc-dimercaptosuccinic acid ([ 99m Tc]DMSA) is reduced from 16.2 ± 2.8% to −0.3 ± 2.1% and from 16.7 ± 10.1% to 2.2 ± 10.6% with [ 111 In]octreotide. Absolute quantitative in vivo SPECT is possible without explicit system matrix measurements. An absolute in vivo quantification error smaller than 5% was achieved and exemplified for both [” m Tc]DMSA and [ 111 In]octreotide.